Routledge handbook of democracy and security - Weinberg, Leonard; Francis, Elizabeth; Assoudeh, Eliot (Routledge, Taylor & Francis Group, 2021)
"This handbook explores how democracies around the world seek to balance their democratic values with the requirement to protect their citizens from the threat of politically motivated violence. Over the past few decades, the majority of the world's democracies have had to confront serious security threats, and in many instances these challenges have not come from rival states but from violent groups. This volume offers readers an overview of how some democracies have responded to such threats. It examines the extent to which authorities have felt compelled to modify their laws to evade what would ordinarily be regarded as protected rights such as personal privacy, freedom of movement, and freedom of speech. Grounded in historical analysis, each of the sections addresses past and emerging security threats; legal and legislative responses to them; successful and unsuccessful efforts to reconcile democracy and security; and a range of theoretical questions. The case studies provided vary in terms of the durability of their democratic systems, level of economic development and the severity of the threats to which they have been confronted. The volume is divided into three thematic parts: Strong Democracies: United States, Great Britain, France, Germany, Italy, Spain, Australia, New Zealand, and Israel Challenged Democracies: India, South Africa, Brazil, Argentina, and Romania Fragile Democracies: the Philippines and Nigeria This book will be of much interest to students of democracy, security studies, political philosophy, Asian politics, Middle Eastern politics, African politics, West European politics, and IR in general"--